Shelf life of indigenous Tengkawang butter: storage kinetic and effect of antioxidant to oxidation stability index - Darmawan, Muhammad Arif; Arya Ramadhan, Muhammad Yusuf; Curie, Catia Angli; Muryanto, .; Sahlan, Muhammad; Utami, Tania Surya; Abd-Aziz, Suraini; Gozan, Misri (Elsevier, 2023)
Tengkawang butter is an indigenous and traditional butter from Borneo that can be a lipid source for pharmaceutical and food applications. Studies found that Tengkawang butter is a cheaper cocoa butter substitution without compromising its quality. However, the current storage method is still very traditional, resulting in faster deterioration of Tengkawang butter. This study aims to calculate and evaluate the storage kinetics model with the Arrhenius model and the tengkawang butter oxidation stability index analysis. Storage conditions were carried out at temperatures of −5, 5, 24, and 60 °C to predict the tengkawang butter storage kinetics model. The addition of antioxidants such as ascorbic acid, tocopherol, and lignin to tengkawang butter help increase the oxidation stability index. The kinetics of the tengkawang butter acidity and peroxide models followed a zero-order reaction with activation energy values of 11.139 kJ mol−1 and 12.320 kJ mol−1, respectively. The prediction model for acidity is Acidity = 4.417–7.903t exp (−11,139/RT), and the model for peroxide is peroxide = 2.155–10.998t exp (−12,320/RT). The oxidation stability index values at 22 °C and the rate of oxidation when the temperature rises by ten degrees (Q10) of tengkawang butter, tengkawang butter with ascorbic acid, tengkawang butter with tocopherol, and tengkawang butter with lignin were 66,896 and 2.815; 224,680 and 1.993; 106,120 and 2.725; 81,658 and 2.961, respectively. The kinetic and oxidation stability index model data can be used as a reference for storage and preserving products made from tengkawang butter.